Arthur's camp-out - Hoban, Lillian ([New York] : HarperCollins, 1993)
Bored with spring vacation, Arthur decides to go alone on an overnight field trip in the woods behind his house.
"Level 2, grades 1-3"--Cover.
Booklist.
Horn Book Starred.
School Library Journal.
2.9
K-3
Keywords: Arthur (Fictitious character : Hoban) -- Fiction; Camping -- Fiction; Chimpanzees -- Fiction; Arthur (Fictional character : Hoban) -- Fiction; Camping -- Fiction; Chimpanzees -- Fiction; Readers (Elementary).